Tracking ocean heat uptake during the surface warming hiatus - Wei Liu (Nature Portfolio, 2016)
Mechanisms for the warming hiatus are inferred by tracking regional ocean heat uptake in different regions. Here, the authors show that the Indo-Pacific heat redistribution holds the key while the abyssal heat uptake in the Atlantic and Southern Oceans primarily reflects the downward penetration of anthropogenic heat.